Measurement of the WZ production cross section in pp collisions at root s=13 Tev - (:unkn) unknown (ELSEVIER, 2017)
The WZ production cross section in proton-proton collisions at root s = 13 Tev is measured with the CMS experiment at the LHC using a data sample corresponding to an integrated luminosity of 2.3 fb(-1). The measurement is performed in the leptonic decay modes WZ -> lVl'l', where l,l'=e,mu. The measured cross section for the range 60<m (l'l') <120 GeV is sigma(pp -> WZ) = 39.9 +/- 3.2(stat)(2.9)(-3.1)(syst)+/- 0.4(theo)+/- 1.3(lumi)pb, consistent with the standard model prediction.
Keywords: CMS; Physics; Electroweak; ZZ PRODUCTION; DISTRIBUTIONS